Neurotransmitter Availability and Anti-Inflammatory and Antioxidant Effects of Subacute Administration of Aloysia gratissima (Gillies & Hook) Tronc. and Rutin in Female Wistar Rats - Gênifer Erminda Schreiner; Elizandra Gomes Schmitt; Gabriela Escalante Brittes; Laura Smolski dos Santos; Luana Tamires Maders; Itamar Luís Gonçalves; Sílvia Muller de Moura Sarmento; Nessana Dartora; Vanusa Manfredini (MDPI AG, 2024)
Background: Levels of chronic inflammation, oxidative stress, and neurotransmitter availability are altered in depressed patients and can be used as biological markers. This study aimed to analyze these markers in female Wistar rats under chronic inflammation induced by E. coli lipopolysaccharide (LPS), treated with aqueous extract of A. gratissima and rutin, the major flavonoid of its extract. Methods: Thirty female Wistar rats under a chronic inflammatory regimen induced by 1 mg/kg i.p. of LPS were divided into six experimental groups: control (1), treated with fluoxetine 5 mg/kg (2), rutin at 50 mg/kg (3) or 100 mg/kg (4), aqueous extract of A. gratissima 100 mg/kg (5), and co-treatment with 50 mg/kg of extract and 10 mg/kg of rutin (6). Treatments were administered by gavage for 15 days. Results: Oxidative damage to proteins and lipids was lower in group 6 compared to group 2. Pro- and anti-inflammatory cytokines increased in group 1 but not in group 2, indicating a relationship with depression. Similar effects were observed in the treated groups, showing no significant differences from group 2. Neurotransmitter levels of dopamine and serotonin were low in group 1, and all treatments effectively increased them. Additionally, A. gratissima extract at 100 ppm increased locomotor activity in planarians. Conclusions: This study demonstrates the effectiveness of the LPS induction model in subacute experimental designs and the potential antidepressant effect of the treatments due to their antioxidant and anti-inflammatory properties, and ability to increase neurotransmitter levels.